Interactive effects among L-carnitine, paylean (ractopamine⋅HCl), and dietary energy density on commercial finishing pig growth performance and carcass characteristics - James, B.W.; Owen, K.Q.; Woodworth, J.C.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Growth performance and carcass characteristics were evaluated on 1,104 pigs fed combinations of L-carnitine, Paylean, and added fat in a 2 × 2 × 2 factorial arrangement. Dietary treatments of L-carnitine (0 or 50 ppm) and fat (0 or 6%) were initiated at approximately 97 lb. Paylean (0 or 9 g/ton) was fed for the last 4 weeks prior to market. Supplementing dietary carnitine did not affect (P>0.25) growth performance of pigs between 97 to 203 lb. The addition of 6% dietary fat improved (P<0.01) ADG and F/G during this period. During the last 4 weeks of the experiment, when Paylean was fed, a carnitine × Paylean interaction was observed (P<0.04) for ADG and F/G. Both carnitine and Paylean improved growth performance; however, the responses were not additive. Pigs fed added fat had improved (P<0.05) feed efficiency during the Paylean supplementation period. A carnitine × Paylean interaction (P<0.03) was observed for fat thickness and percentage lean. Fat thickness decreased and lean percentage increased in pigs fed carnitine or Paylean, but the responses were not additive. Pigs fed added fat had greater (P<0.01) fat thickness and lower percentage lean than pigs not fed added fat. A carnitine × Paylean × fat interaction was observed (P<0.04) for longissimus muscle area. In general, adding carnitine, Paylean or fat to the diet increased longissimus muscle area; however, the responses were not fully additive. Carcass weight was greater (P<0.01) for pigs fed 6% added fat and tended (P<0.07) to be greater for pigs fed carnitine. Adding Paylean to the diet increased (P<0.04) ultimate longissimus pH and reduced drip loss as measured by the filter paper method. Similar to other experiments, adding carnitine to the diet tended to decrease drip loss (P<0.06) as measured by the suspension method. These results suggest that adding Lcarnitine and Paylean to the diet increases ADG and that L-carnitine, Paylean, and fat improve feed efficiency when fed to late finishing pigs reared in a commercial facility. These data also support our previous research that demonstrated improvements in carcass characteristics of pigs fed L-carnitine.
Keywords: Carnitine; Paylean; Meat quality; Swine